You're more powerful than you think : a citizen guide to making change happen - Liu, Eric (2017)
This is an age of epic political turbulence in America. Old hierarchies and institutions are collapsing. From the fracturing of the major political parties, to the spread of bottom-up movements like Black Lives Matter and $15 Now, citizens across the country and across the political spectrum are reclaiming power. It is no longer the exclusive domain of CEOs, political elites, and insiders from either political party. And the question that today's rising citizens have to face is: Are you ready? Do you understand power? And if you want to make change in the world, do you know how? The answers to all these questions are provided in Eric Liu's book. In its pages, Liu lays out the elements and the strategies of citizen power, showing when to create a hashtag, when to call your Congressman, and when to take to the streets. (When you go, don't forget your camera.) Above all, Liu reminds us that *someone* always has power, which means if you're not participating, you're surrendering. Published in the early days of a new presidency, this book is not just a manual for power but an inspiring call to action. As Liu shows, voting is just one way of inciting change. So is protesting. What happens after the election, and after the march through the streets, is the real test of whether we the people can truly be we the powerful
Prologue: Immokalee and Pottersville -- The age of citizen power -- How to understand power -- How to practice power -- The why of power -- Epilogue: They/we
Includes bibliographical references (pages 209-222)
Keywords: Political participation -- United States; Power (Social sciences) -- United States